(untitled) (Journal of actual problems of jurisprudence, 2021)
This article discusses the problems of combating illicit trafficking in narcotic drugs and psychotropic substances. Nowadays, this problem has become as global as environmental pollution, the human immunodeficiency virus, which differentiates into acquired immunodeficiency syndrome, in other words, into AIDS. The world community should not ignore this issue. Drug abuse leads to domestic conflicts in the family, the moral decay of society, and then the state, and this is not to mention the health problems, both physical and spiritual, of citizens. A person’s craving for drugs has led to the proliferation of drug crime, which is a type of organized crime and represents a public danger. The organization and legal support of measures to combat illicit trafficking in drugs and psychotropic substances is the task of each State. However, the fight against this type of crime within the framework of only one State is too difficult to implement. Countering illicit drug trafficking should be carried out in the form of cooperation between States in this area. The scope of international cooperation in combating drug trafficking is determined taking into account the policies of the States that participate in it. Key words: illegal drug trafficking; narcotic drugs; drug trafficking; drug trafficking; psychotropic substances, drug market, anti-drug measures, anesthesia, legalization, criminal policy